2021
DOI: 10.52095/gp.2021.3838.1027
|View full text |Cite
|
Sign up to set email alerts
|

Association of social stigma of COVID-19 with work satisfaction, burnout and fatigue among healthcare workers in Nepal

Abstract: Objective: Stigma towards COVID-19 patients has been reported in various media news, including negative behaviour among healthcare workers (HCWs) towards COVID-19 patients, which could affect the professional quality of life for these HCWs. AIMS: We aimed to assess stigma related to COVID-19 patients among HCWs and explore its impact on their professional quality of life during the COVID-19 pandemic in Nepal. Methods: An online cross-sectional study was carried out among 421 HCWs (health assistants 35.6%, nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Stigmatizers' demographics have been investigated in the literature (Abuhammad et al, 2021 ; Cassiani-Miranda et al, 2021 ; Hossain et al, 2021 ; Jiang et al, 2021 ; Li et al, 2021 ; Singh et al, 2021 ; Zhang et al, 2021 ). We identified two aspects highlighting the influence of stigmatizers' demographics: (1) certain demographics of stigmatizers are associated with less stigmatizing attitudes toward (suspected) patients and survivors because they reflect higher knowledge about COVID-19 (e.g., higher education and healthcare occupations vs. general public), and (2) certain demographics of stigmatizers are associated with more stigmatizing attitudes toward (suspected) patients and survivors because they reflect lower resources (e.g., rural vs. urban residence) and higher risk of COVID-19 infection (e.g., regions close to the origin location of COVID-19 and old age).…”
Section: Antecedents Of Stigma Toward (Suspected) Patients and Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigmatizers' demographics have been investigated in the literature (Abuhammad et al, 2021 ; Cassiani-Miranda et al, 2021 ; Hossain et al, 2021 ; Jiang et al, 2021 ; Li et al, 2021 ; Singh et al, 2021 ; Zhang et al, 2021 ). We identified two aspects highlighting the influence of stigmatizers' demographics: (1) certain demographics of stigmatizers are associated with less stigmatizing attitudes toward (suspected) patients and survivors because they reflect higher knowledge about COVID-19 (e.g., higher education and healthcare occupations vs. general public), and (2) certain demographics of stigmatizers are associated with more stigmatizing attitudes toward (suspected) patients and survivors because they reflect lower resources (e.g., rural vs. urban residence) and higher risk of COVID-19 infection (e.g., regions close to the origin location of COVID-19 and old age).…”
Section: Antecedents Of Stigma Toward (Suspected) Patients and Survivorsmentioning
confidence: 99%
“…For example, one study found that the epidemic proximity of one's role, ranging from peripheral (e.g., general public) to intermediate (e.g., family members of COVID-19 patients) to center (e.g., HCWs, police), negatively predicts stigmatization and discrimination toward suspected patients (Chen et al, 2021a ). A web-based cross-sectional study among HCWs also found that having served COVID-19 patients positively predicts acceptance of COVID-19 patients and negatively predicts fear of COVID-19 patients—two dimensions of stigma toward COVID-19 patients (Singh et al, 2021 ).…”
Section: Antecedents Of Stigma Toward (Suspected) Patients and Survivorsmentioning
confidence: 99%
“…For example, one study found that the epidemic proximity of one's role, ranging from peripheral (e.g., general public) to intermediate (e.g., family members of COVID-19 patients) to center (e.g., HCWs, police), negatively predicts stigmatization and discrimination toward suspected patients 74 . A web-based cross-sectional study among HCWs also found that having served COVID-19 patients positively predicts acceptance of COVID-19 patients and negatively predicts fear of COVID-19 patients-two dimensions of stigma toward COVID-19 patients 72 .…”
Section: Social Interaction (With the Stigmatized Group) Stigmatizers...mentioning
confidence: 95%
“…Demographics. Stigmatizers' demographics have been investigated in the literature 67,68,69,70,71,72,73 . We identified two aspects highlighting the influence of stigmatizers' demographics: (1) certain demographics of stigmatizers are associated with less stigmatizing attitudes toward (suspected) patients and survivors because they reflect higher knowledge about COVID-19 (e.g., higher education, and healthcare occupations versus general public), and (2) certain demographics of stigmatizers are associated with more stigmatizing attitudes toward (suspected) patients and survivors because they reflect lower resources (e.g., rural versus urban residence) and higher risk of COVID-19 infection (e.g., regions close to the origin location of COVID-19, and old age).…”
Section: Stigmatizermentioning
confidence: 99%
“…9 Moreover, work-related fatigue increases medical error, 10 absenteeism and turnover among nurses whereas decreases morale. 11 In Nepalese context, the issue of compassion fatigue and burnout among nurses is overlooked and there have been fewer studies 12,13 which address these situations among health workers. Hence, this study aimed to assess the compassion fatigue, burnout and compassion satisfaction among nurses working in a tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%